Urbanisasi dalam Tinjauan Historis: Studi Kasus Pemukiman Kumuh di Kelurahan 3-4 Ulu Kota Palembang, 2010-2020 - Maharani, Alda Risma; Wargadalem, Farida Ratu; Safitri, Sani (Universitas Hamzanwadi, 2024)
This article examines the urbanization that occurred in slum settlements in Subdistrict 3-4 Ulu, Palembang City from 2010-2020. The focus of this article is on the ethnic diversity of living in slums and the socioeconomic problems faced as a result of urbanization. The research process starts from searching for data to writing articles using historical methods. This article aims to identify the impact of social exclusion and marginalization on ethnic minority groups as well as environmental damage due to urbanization. The research results show that Subdistrict 3-4 Ulu, Palembang City is classified as a very slum settlement. This can be seen in slum housing locations, lack of infrastructure, high unemployment rates, and limited access to education and health services. The studies that have been carried out contribute to providing useful insights into designing sustainable development policies in the future by proposing various mitigation efforts and solutions, including government measures, housing, and infrastructure improvement programs, as well as the importance of social integration and community participation.